Increasing Student Learning Activeness by Using Puzzle Media in Learning Pancasila Education at SMPN 38 Palembang - Parianda, Putria Juni; Alfiandra, Alfiandra; Hasdawaty, Ervinna (CV. Rayyan Dwi Bharata, 2024)
This research was motivated by the problem of low learning activeness of class VIII students in junior high schools. Students look passive, lack self-confidence, and show low learning motivation in the learning process. This research aims to increase students' learning activeness through the use of crossword puzzle and word search puzzle media in learning Pancasila Education class VIII.6 at SMP Negeri 38 Palembang. This research was carried out using the classroom action research method which was carried out over 2 cycles where each cycle consisted of 1 meeting and 1 assessment which consisted of 4 stages, namely: planning, action, reflection and evaluation. The subjects in this research were all students in class VIII.6 of SMP Negeri 38 Palembang, consisting of 15 male students and 17 female students. This research was conducted using a quantitative approach with observational data collection techniques. Observations were carried out by observing observers whose results were analyzed using percentage descriptive data analysis techniques. This research shows that the use of crossword puzzle and word search puzzle media in learning can increase the learning activity of class VIII.6 students at SMP Negeri 38 Palembang. This can be seen from the observation results obtained in the pre-cycle which show that students' learning activeness has a percentage of 49.78%, then in cycle 1 it increased by 24.66% to 74.44%, and in cycle 2 it increased by 14.40% to 88.84%. This shows that the use of crossword puzzle and word search puzzle media in learning can increase the learning activity of students in class VIII.6 SMPN 38 Palembang.